2007
DOI: 10.1007/bf03175060
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a quaternary ammonium compound against planktonic and sessile populations of differentLegionella pneumophila strains

Abstract: Efficacy of Gemacide PN-50 TM (a quaternary ammonium compound) as a commercial formulation recommended for disinfecting heat exchangers was determined for both planktonic and sessile populations of various Legionella pneumophila strains. The quaternary ammonium compound (QAC) was preferred as an alternative due to the emerging resistance of potentially pathogenic bacteria against different biocides. Planktonic L. pneumophila strains were suspended in tap water while sessile ones were grown on stainless steel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, since bacteria (and notably environmental/clinical isolates) grown as a biofilm are more resilient to antimicrobial action (Kimiran-Erdem et al 2007), one of the problems associated with biofilm efficacy test, apart the type of protocol to be used, is that higher a concentration of a biocide will most probably have to be used to ensure efficacy. This will lead to increase in costs for the manufacturer and increase in levels of biocide released in the environment.…”
Section: Requirement For New Methodologies For Risk Assessment Of the Effect Of Biocide Usage On Antibiotic Resistancementioning
confidence: 99%
“…However, since bacteria (and notably environmental/clinical isolates) grown as a biofilm are more resilient to antimicrobial action (Kimiran-Erdem et al 2007), one of the problems associated with biofilm efficacy test, apart the type of protocol to be used, is that higher a concentration of a biocide will most probably have to be used to ensure efficacy. This will lead to increase in costs for the manufacturer and increase in levels of biocide released in the environment.…”
Section: Requirement For New Methodologies For Risk Assessment Of the Effect Of Biocide Usage On Antibiotic Resistancementioning
confidence: 99%
“…In general, oxidizing biocides were found to be more effective than non-oxidizing ones against legionellae [5,16,17]. In the present study oxidizing biocide (CSHP) was found more effective than non-oxidizing biocide (BNPD) in terms of contact times, log reductions and recommended concentrations.…”
Section: Resultsmentioning
confidence: 50%
“…At the time points given above, biocide-bacteria suspensions were incubated at 37°C and aliquots were processed as described above. The controls consisted of Legionella bacteria in Cl 2 -free sterile tap water containing no biocide [16,17]. All of the experiments were done in triplicates.…”
Section: Determination Of Biocidal Activitymentioning
confidence: 99%